Peran Direktur Badan Usaha Milik Desa Dalam Pengelolaan Unit Usaha Pada BUMDes eMHa Desa Melirang - Devlin Harnedicta Fajriyah; Endang Indartuti; Dida Rahmadanik (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The village is the smallest unit in the government structure in Indonesia which plays an important role in managing local resources and development at the village level. Law Number 6 of 2014 concerning Villages states that village governments are responsible for managing government programs aimed at the interests of the community. Village-Owned Enterprises (BUMDes) have become an important part of the government's efforts to develop the rural economy and reduce the economic gap between urban and rural areas. This research explores the role of BUMDes directors in managing BUMDes using Alif's theory in Nurdin (2014) with four indicators: regulator, dynamist, facilitator and catalyst. This research uses a descriptive qualitative method, which aims to produce descriptive data in the form of written or spoken words from people and behavior observed from the phenomena that occur.